2021
DOI: 10.32854/agrop.v13i12.1737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of flowering and production inducers in the Mexican lime (Citrus aurantifolia Swingle)

Abstract: Objective: To evaluate new hormonal and biostimulant products to induce flowering of Mexican lime (Citrus aurantifolia Swingle) for winter production at the state of Guerrero, Mexico. Design/methodology/approach: Prohexadione calcium (PHD-Ca), cytokinins, paclobutrazol, biuretic urea, granulated urea (46%) and a control were evaluated. Results: There are differences between treatments for the number of flowers and number of fruits (Pr>0.0411 and 0.048); regard the “number of flowers” variable, paclobutrazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Many studies have reported that drought can induce flowering in several plant species, including durian [10,11], mango [15], citrus fruits [9], longan [13], lime [12], loguat [14], and mangosteen [17]. A drought period lowers soil moisture and increases soil temperature.…”
Section: -3-soil Temperature and Moisture At Four Depth Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported that drought can induce flowering in several plant species, including durian [10,11], mango [15], citrus fruits [9], longan [13], lime [12], loguat [14], and mangosteen [17]. A drought period lowers soil moisture and increases soil temperature.…”
Section: -3-soil Temperature and Moisture At Four Depth Levelsmentioning
confidence: 99%
“…Many studies have shown that mangosteen reproductive phenology (i.e., flowering and fruiting) is associated with climatic conditions (e.g., rainfall, temperature, radiation levels, and photoperiod), height above sea level, availability of shade, and geographical locations [2][3][4][5][6][7][8]. Drought-inducing flowering has been reported in several plant species, including citrus fruits [9], durian [10,11], lime [12], longan [13], loguat [14], mango [15], and mangosteen [5,16,17]. Many studies have reported that drought-inducing flowering in mangosteens with 15-30 dry days for flower bud formation and flowering, occurs naturally after the dry period [2,3,5,[17][18][19].…”
mentioning
confidence: 99%